Analysis and Design of a New Type of Coupler and Phase Shifter Based on Semi-elliptical Edge-coupled Structure - Lo, Yew Chiong (2019)
The analysis and design of wideband directional coupler and phase shifter using semi-elliptical edge-coupled structure are presented. The structures consist of two semi-elliptical patches on the top layer and an elliptical defected ground plane on the bottom layer to increase the coupling coefficient and operating bandwidth. The proposed structure is modelled as a four-port device. Two of the ports are open circuited for the case of phase shifter. The coupling coefficient can be expressed in terms of even and odd mode characteristic impedances. For phase shifter design, the amount of phase shift can be controlled by changing the coupling coefficient. Even and odd mode analysis is carried out and sets of design graphs are formulated to facilitate the design of the directional coupler and phase shifter on substrate with dielectric constant of 2.2 and 3.38. Using the design graphs, the physical dimensions of the directional coupler and the phase shifter can be obtained. An approximate equation is also formulated to estimate the center frequency of the device. For the case of directional coupler, designs are made with coupling factor, C of 10dB ± 1 dB. The reflection coefficient, insertion loss, coupling, and isolation iii are first simulated. The designs are fabricated on Rogers RT/Duroid 5880 and RO4003C with different substrate thicknesses and tested using a vector network analyser. The fabricated couplers have a reflection coefficient of better than -18 dB, isolation of better than 22 dB, and insertion loss of less than 1 dB. The proposed coupler design exhibits wideband characteristics, with a bandwidth ratio of 2.4. For the case of phase shifter, designs are made with coupling factor, C of 5 dB and 6 dB. The reflection coefficient, insertion loss, and differential phase shift are first simulated and the designs are fabricated on Rogers RT/Duroid 5880 and RO4003C with different substrate thicknesses. The bandwidth ratio are approximately 2.4 and 2.1 for coupling of 5 dB and 6 dB, respectively. The phase shifts are 80 ± 3º and 97.5 ± 3.5º for coupling of 5 dB and 6 dB, respectively. All phase shifters have reflection coefficient better than -10 dB, and insertion loss better than 1 dB throughout the operating frequency range. These results show that the proposed design exhibits wideband characteristics with low phase ripple. The proposed structure is compact, simple, easy to fabricate and low cost.